Official language use in Berehove in 1919-1920 - Szakal Imre; Szakál Imre; Сакал Імре; Mádi Gabriella; Маді Габріелла (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. The political map of East-Central Europe changed after the First World War. But this transformation also affected many different aspects of everyday life. In particular, the years of transition from the collapsing empires to the new republics offer rich research opportunities. In this paper, we have tried to explore one aspect of this transition at the interface of history and sociolinguistics. In a peripheral small town in the Czechoslovak Republic, we have used archival sources to investigate the characteristics of the official language use at the beginning of the consolidation of the new state power. Our study also seeks to find answers to the question of what influenced the different language-speaking actors at different levels of the administration, and what bargains were struck in everyday life that might have determined other aspects of the transition.

Резюме. Політична карта Центрально-Східної Європи змінилася після Першої світової війни. Але ця трансформація також вплинула на багато різних аспектів повсякденного життя. Зокрема, роки переходу від імперій, що розпалися, до нових республік відкривають багаті можливості для досліджень. У цій статті ми спробували дослідити один з аспектів цього переходу на стику історії та соціолінгвістики. На прикладі невеликого периферійного містечка в Чехословацькій Республіці ми використали архівні джерела, щоб дослідити особливості використання офіційних мов на початку консолідації нової державної влади. Наше дослідження також прагне знайти відповіді на питання, що впливало на різних мовних акторів на різних рівнях адміністрації, і які угоди були укладені в повсякденному житті, що могли визначити інші аспекти перехідного періоду.

Kelet-Közép-Európa politikai térképe az első világháború után megváltozott. Ez az átalakulás a mindennapi élet számos területét is érintette. Különösen az összeomló birodalmakból az új köztársaságokba való átmenet évei kínálnak gazdag kutatási lehetőségeket. Ebben a tanulmányban ennek az átmenetnek egy aspektusát igyekeztünk feltárni a történelem és a szociolingvisztika határterületén. A Csehszlovák Köztársaság egyik periférikus kisvárosa esetén vizsgáltuk levéltári források segítségévela hivatalos nyelvhasználat jellemzőit az új államhatalom megszilárdulásának kezdetén. Tanulmányunk arra is választ keres, hogy mi befolyásolta a különböző nyelveket beszélő szereplőket a közigazgatás különböző szintjein, milyen alkukat kötöttek a mindennapi életben, amelyek meghatározhatták az átmenet más mozzanatait.
Використання офіційної мови в Берегові в 1919-1920 рр
Hivatalos nyelvhasználat Beregszászban 1919-1920-ban
https://aab-philologica.kmf.uz.ua/aabp/issue/view/5/9
Keywords: Transcarpathia; Subcarpathian Rus; multilingualism; official language use